THE EVOLUTION OF CARGO SHIPS IN THE MALAYSIAN MARITIME INDUSTRY - RAMLAN, MUHAMMAD SYAZWAN; NIK HARIRY, NIK NURHALIDA (Journal of Maritime Logistics, 2023)
The maritime industry plays an important role in facilitating international trade and economic growth, making it important for Malaysia to remain at the forefront of technological advancements in the design and operation of cargo ships. This abstract investigates the evolution of cargo ships in the context of the Malaysian maritime industry. By examining historical developments, technological innovations, and regulatory changes, this study aims to shed light on the transformative journey of cargo ships and their impact on the nation’s trade and shipping sector. This study aims to analyze whether this cargo ship revolution is beneficial to the Malaysian maritime industry and to identify the impact of the evolution of large cargo ships in the Malaysian maritime industry. It explores the transition from traditional wooden ships to steel-hulled ships and the emergence of containers, which revolutionized cargo handling efficiency. The results of this study also talk about the revolution of cargo ships, namely autonomous ships, which have transformed cargo ships into sophisticated and efficient ships. Smart integration into cargo ships not only improves operational efficiency but also optimizes fuel consumption, resulting in a reduced environmental impact. In addition, it also tells the impact of the cargo revolution and cargo revolution beneficial to the existence of automatic ships. In this study, the researcher also conducted an interview session with the operation manager of Lumut Maritime Terminal (LMT), a ship captain from (MISC) company, and a Chief Engineer First Class from the Java Offshore Company. The results of the interviews will be analyzed using content analysis to identify the effects and benefits of this cargo ship revolution. Finally, this research aims to provide valuable insights to industry stakeholders, and researchers who wish to understand the dynamic evolution of cargo ships and their importance in the context of Malaysian maritime development.